CNT/AgNW Multilayer Electrodes on Flexible Organic Solar Cells - Yang, Min Kyu; Lee, Jeon-Kook (KOREAN INST METALS MATERIALS, 2020)
In this study, the fabrication of transparent CNT/AgNW multilayer electrodes on PET substrates using a spray coating process is investigated. A CNT/AgNW multilayer electrode exhibited a R(sh)of 50 Omega/square with a transparency of 94% at 500 similar to 550nm wavelength without substrate. We examined the effects of the sheet resistance and transparency of CNT/AgNW multilayer electrodes based on the performance of the OSC cells. The use of sprayed CNT/AgNW multilayer electrodes will advance the mass production of inexpensive and highly efficient flexible polymer organic solar-cell based films using a roll-to-roll based process. [GRAPHICS] .